The effectiveness of employing the ICT Diploma program in developing administrative work in the first Zarqa district schools from the point of view of principals and directorate employees - Mohummad, Aladdin Eid Zohdi (Journal of Educational and Psychological Sciences, 2022)
This study aimed to identify the effectiveness of employing the ICT Diploma program in developing administrative work in schools from the point of view of directorate employees and school principals in Zarqa first Directorate, the study used the descriptive analysis approach, questionnaire has been used it consisted from (17) paragraph, the sample of study consisted from (120) female and male employee. However, the result of SPSS analysis shown that the level employing the ICT Diploma program in developing administrative work in schools from the point of view of directorate employees and school principals was high with a average (3.68 out of 5), The finding also showed there wasn’t any statistically significant differences at (α≤0.05) refers to employee sex (male and female). In addition, there were statistically significant differences between the years of employee years of experience in favor of (10 years and less). In light of these results, the researcher recommended a set of recommendations, the most important of which is the necessity for workers in the education sector to benefit from the ICT diploma program in developing the educational process.
Keywords: Effectiveness; ICT Diploma Program; Administrative Work